2017
DOI: 10.24123/aipj.v33i1.1439
|View full text |Cite
|
Sign up to set email alerts
|

The Relationships Between Job Embeddedness, Person-Organization Fit, and Turnover Intention

Abstract: This study aim to examine the relationships between job embeddedness, person-organization fit (POF), and turnover intention. Job embeddedness is a variety of conditions that make individuals feel attached to their job and organization. Person-organization fit is the compatibility between the characteristics of individuals and their organizations. Turnover intention is an employee’s conscious desire to leave his or her organization. This study was conducted among employees of a retail company in West Jakarta. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 17 publications
(40 reference statements)
1
3
0
Order By: Relevance
“…Furthermore, staff nurses feel their jobs are compatible with their goals and values get good match with this organization and their loss by leaving their job increase. This is the same view of, Ciptaningtyas (2017) (51) who examined the relationships between Job embeddedness, person-organization fit, and turnover intention and reported that the greater the compatibility or suitability between employees and their organization in goals and values, the greater the employees" attachment to their work and preserve benefits received. This result agreed with, Trastek (2014) & Ferreira, (2017) (52,53) who reported that, ethical behavior of servant leadership correlates to job embeddedness dimensions.…”
Section: Discussionsupporting
confidence: 58%
“…Furthermore, staff nurses feel their jobs are compatible with their goals and values get good match with this organization and their loss by leaving their job increase. This is the same view of, Ciptaningtyas (2017) (51) who examined the relationships between Job embeddedness, person-organization fit, and turnover intention and reported that the greater the compatibility or suitability between employees and their organization in goals and values, the greater the employees" attachment to their work and preserve benefits received. This result agreed with, Trastek (2014) & Ferreira, (2017) (52,53) who reported that, ethical behavior of servant leadership correlates to job embeddedness dimensions.…”
Section: Discussionsupporting
confidence: 58%
“…However, in a study conducted in West Jakarta, Ciptaningtyas et al. (2017) found embeddedness but not PO predicted turnover intentions. Thus, although we know that misfit is harmful psychologically to individuals, if they are embedded they are more likely to stay in role and suffer those consequences.…”
Section: A Personal History and Introduction To The Conundrumsmentioning
confidence: 94%
“…Included studies The following studies were included in the current meta-analysis. Supplementary data can be found online at https://tinyurl.com/appendix-metaanalysis-sea Thai Samples: Ampofo et al (2017); Dechawatanapaisal (2017); Dechawatanapaisal (2018a); Dechawatanapaisal (2018b); Popaitoon and Techalertsuwan (2020); Sawathwej and Setthakorn (2019); Setthakorn (2019); Setthakorn (2020); Suruchthanano (2021); Tantiboontaweewat and Maneesri (2013); Wissawapaisal and Chaiprasit (2015) Indonesian Samples: Ananda and Pane (2017); Atan and Purba (2018); Bambacas (2012); Ciptaningtyas et al (2017); Kismono (2011); Maska and Riyanto (2020); Purba et al (2015); Purba et al (2016); Ratnawati et al (2020); Savira (2018); Sudarti et al (2021) …”
mentioning
confidence: 99%
“…Indonesian Samples: Ananda and Pane (2017); Atan and Purba (2018); Bambacas (2012); Ciptaningtyas et al (2017); Kismono (2011); Maska and Riyanto (2020); Purba et al (2015); Purba et al (2016); Ratnawati et al (2020); Savira (2018); Sudarti et al (2021)…”
mentioning
confidence: 99%